Republics at War, 1776-1840 Revolutions, Conflicts, and Geopolitics in Europe and the Atlantic World - Serna, P.; Serna, P.; Francesco, A. De.; Francesco, A. De.; Miller, J.; Miller, J. (War, Culture and Society, 1750 –1850, 2013)
This collection probes the troubling connections between war and republic during Revolutionary era, 1776-1840. It presents the work of an international team of scholars, some of them in English for the first time.